1998
DOI: 10.1007/s004200050267
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiology study of lung function changes of toluene diisocyanate foam workers in the United Kingdom

Abstract: This study does not provide evidence that there is a TDI-related decline in FEV1 and FVC in workers exposed to less than the United Kingdom 8-h occupational exposure limit of 5.8 ppb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
(38 reference statements)
5
17
0
Order By: Relevance
“…Based on pulmonary function results from larger and more recent longitudinal studies where the TWA TDI concentrations were 65 ppb, Ott andco-workers (2002, 2003) concluded that ''these studies do not provide evidence of an accelerated rate of decline in FEV1 among TDI-exposed employees''. This conclusion is supported by the results of a prospective study of 251 TDI polyurethane foam production workers in the UK followed over a period of 17 years (Clark et al, 2003). The decreases in FEV1 and FVC seen in this study were unrelated to TDI exposure level and were comparable to those measured in other populations not exposed to TDI.…”
Section: Respiratory Tract Effects -Irritation and Lung Decrement Notsupporting
confidence: 79%
“…Based on pulmonary function results from larger and more recent longitudinal studies where the TWA TDI concentrations were 65 ppb, Ott andco-workers (2002, 2003) concluded that ''these studies do not provide evidence of an accelerated rate of decline in FEV1 among TDI-exposed employees''. This conclusion is supported by the results of a prospective study of 251 TDI polyurethane foam production workers in the UK followed over a period of 17 years (Clark et al, 2003). The decreases in FEV1 and FVC seen in this study were unrelated to TDI exposure level and were comparable to those measured in other populations not exposed to TDI.…”
Section: Respiratory Tract Effects -Irritation and Lung Decrement Notsupporting
confidence: 79%
“…Exposure to diisocyanate monomers has been assessed in various epidemiologic studies. In the majority of these studies, mean or maximum exposure levels are reported for a population in which a measure of disease frequency is investigated (19)(20)(21)(22)(23)(24)(25). However, few studies have considered the issue of quantitative exposure response in isocyanate asthma (26).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory symptoms among industries workers have been reported by several authors. A number of studies have reported that workers in industries are exposed to relatively high levels of pulmonary contaminants in their working environment 12) Chemical agents are the commonest reported cause of respiratory irritants, sensitizers and occupational asthma in the United Kingdom 13) Although some studies failed to find respiratory symptoms in workers 14) . Investigations by Valic and Beritic found a significantly increased prevalence of asthma symptoms in tobacco workers compared to that in control subjects.…”
mentioning
confidence: 99%